Polarization Sensitive Solar‐Blind Ultraviolet Photodetectors Based on Ultrawide Bandgap KNb3O8 Nanobelt with Fringe‐Like Atomic Lattice. (14th January 2022) - Ping, Yue; Long, Haoran; Liu, Hui; Chen, Chao; Zhang, Nannan; Jing, Hongmei; Lu, Jiangbo; Zhao, Yiwei; Yang, Zimeng; Li, Wei; Ma, Fei; Fang, Xiaosheng; et al.
Abstract: Low‐dimensional ultrawide bandgap semiconductors demonstrate great potential in fabricating solar‐blind ultraviolet photodetectors. However, the widespread use of detectors is still limited by the low responsivity, large noise, and dark current, and especially few detectors can fulfill the solar‐blind ultraviolet detection and the polarization dependence simultaneously. Herein, a polarization sensitive solar‐blind ultraviolet photodetector based on ultrathin KNb3 O8 nanobelts synthesized via chemical vapor deposition growth, is reported. By selecting suitable substrate and tuning the growth temperature, the nonlayered KNb3 O8 crystal is grown into the quasi‐1D ultrathin nanobelt with thickness in the range of 4.8–120 nm. Density functional theory calculations and experimental results indicate that the ultrathin KNb3 O8 nanobelt possesses an ultrawide bandgap (4.15 eV) as well as unusual in‐plane structural anisotropy. Benefiting from the above features, the ultrathin KNb3 O8 nanobelt‐based device exhibits superior photodetection performances with high responsivity (30 A W −1 ), high detectivity (5.95 × 10 11 Jones), and ultralow dark current (7.1 × 10 −15 A) in the solar‐blind ultraviolet region (230–280 nm). In addition, the KNb3 O8 photodetector displays strong polarization sensitive photoresponse with a linear dichroic ratio of 1.62 at 254 nm. With these remarkable features, the ultrathin KNb3 O8 nanobelt provides great opportunities for designing the next‐generation multifunctional solar‐blind ultraviolet optoelectronic devices. Abstract : A polarization sensitive solar‐blind ultraviolet (UV) photodetector is constructed based on the chemical vapor deposition grown ultrathin KNb3 O8 nanobelts. The high crystallinity, ultrawide bandgap, and intrinsic structural anisotropy of the KNb3 O8 nanobelt offer its detector high responsivity to solar‐blind UV light with large linear dichroism. This work opens up new prospects for developing future multifunctional solar‐blind UV optoelectronic devices.